Nutritional AGEing and RAGEing as a Regulator of the Tumor Microenvironment. (7th June 2021) - Turner, Dave; Krisanits, Bradley; Woods, Pamela; Frye, Callan; Cosh, Sean; Nogueira, Lourdes; Spruill, Laura; Lilly, Michael; Helke, Kristi; Li, Hong; Brown, Shanora; Knowles, Ashley Evans; et al.
Abstract: Objectives: Advanced glycation end products (AGEs) are reactive metabolites formed endogenously by glyoxidative, oxidative and lipoxidative stresses. Foods associated with modern dietary habits are particularly AGE laden but despite increasing epidemiological evidence for oncogenic potential, cause and effect relationships are lacking. The objective was to provide detailed mechanistic insight and in vivo confirmation that AGEs found in the diet are oncogenic drivers of tumorigenesis. Methods: We used the heat driven formation of glyoxidative, oxidative and lipoxidative stresses in experimental mouse chow to reproduce the wide spectrum of the AGEs found in vivo . Syngeneic xenograft and spontaneous prostate and breast cancer mouse models were then fed the AGE specific diets and the effects of chronic AGE consumption on tumor growth assessed. To gain mechanistic insight, human and mouse two compartment co-culture models using primary fibroblasts and matched tumor epithelial cells were then used to assess the effects of AGEs on extracellular crosstalk in the TME. Results: A high impact finding from our research is that consumption of AGEs found in our diet promotes prostate tumor growth, aggression and metastasis by functioning as ligand to the transmembrane receptor for AGE (RAGE). Dietary-AGEs promoted neoplastic growth by functioning as ligand to RAGE expressed in the prostate tumor stroma not tumor epithelium. Dietary-AGE activation of stromal RAGE caused a regulatory program of 'activated fibroblasts' defined by the increased expression of cancer associated fibroblast markers, NFkB, MYC and pro-tumorigenic paracrine secretion. Fibroblast activation was accompanied by decreased expression of androgen receptor (AR) and the increased expression of neuroendocrine differentiation markers in tumor epithelial cells. AGE exposed primary fibroblasts isolated from patient tissue conferred tumor promoting abilities when cultured with patient matched tumor epithelial cells. Conclusions: For the first time these data demonstrate a direct cause and effect relationship between dietary-AGEs and neoplastic growth. This may lay the foundation for strategic self-management strategies aimed at reducing AGE exposure in the diet to reduce cancer incidence and mortality. Funding Sources: NIH/NCI; ACS.